2-Deoxy-D-glucose Alleviates Collagen-Induced Arthritis of Rats and Is Accompanied by Metabolic Regulation of the Spleen and Liver - Wang, Hongxing; Zhang, Nanyang; Fang, Kehua; Chang, Xiaotian (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is significantly associated with glycolysis. This study used 2-deoxy-D-glucose (2-DG), an inhibitor of glycolysis, to treat rats with collagen-induced arthritis (CIA) and investigate the metabolic regulatory mechanism of glycolysis in the disease. 2-DG significantly alleviated CIA. Metabolomics and transcriptomics, as well as their integrative analysis, detected significant changes in the pathways of bile secretion, cholesterol and linoleic acid metabolism in the plasma, liver and spleen during the CIA process and the opposite changes following 2-DG treatment, whereas the expression of the genes regulating these metabolic pathways were changed only in the spleen. In the rat liver, levels of (S)-5-diphosphomevalonic acid in the terpenoid backbone biosynthesis pathway were significantly decreased during CIA progression and increased following 2-DG treatment, and levels of taurochenodeoxycholic acid in the pentose and glucuronate interconversions pathway showed the opposite results. In the spleen, levels of 3-methoxy-4-hydroxyphenylglycol glucuronide in bile secretion and 12(S)-leukotriene B4 in arachidonic acid metabolism were significantly decreased during CIA progression and increased following 2-DG treatment. The changes in the gene-metabolite network of bile secretion in the spleen correlated with a decreased plasma L-acetylcarnitine level in CIA rats and an increase following 2-DG treatment. Our analysis suggests the involvement of spleen and liver metabolism in CIA under the control of glycolysis.